Cryosphere-controlled methane release throughout the last glacial cycle - Serov, Pavel (Science, 2018)
The cryosphere of Arctic regions is undergoing rapid change due to century-scale global warming superimposed on millennial-scale natural climatic perturbations that started at the end of the last glacial cycle approximately 20,000 years ago [Slaymaker and Kelly, 2009]. The cryosphere refers to areas where low temperatures freeze water and form ice in the ocean (sea ice), on land (glaciers, permafrost, snow cover) and beneath the seabed (offshore permafrost) [Harris and Murton, 2005]. These areas may modulate release of greenhouse gases, such as methane and CO2 into the atmosphere, both from the ocean through a barrier effect of sea ice, and also from land through a sealing effect of permafrost, glaciers and associated gas hydrates. Today’s cryosphere shows rapid degradations in various regions of the Arctic, which may act as a climate change amplifier if outgassing of greenhouse gases from formerly stable gas hydrates and biogenic and thermogenic sources reaches the atmosphere [Callaghan et al., 2011]. While gas hydrates are widely distributed within cryosphere, they are only stable under low temperature and high pressure conditions [Ginsburg, 1998]. Gas hydrate of natural gas is a crystalline water-based structure physically resembling ice and incorporating large concentrations of hydrocarbon gases (predominantly methane; 1 cm3 of methane hydrate contains 150 cm3 of methane) [Sloan, 2008]. With this in mind, the doctoral thesis focuses on gas hydrate dynamics in response to the degradation of the cryosphere across the Barents Sea and South Kara Sea continental shelves throughout the last 35,000 years. This doctoral thesis was undertaken at the Department of Geoscience, UiT – The Arctic University of Norway, Tromsø, from January 2015 to December 2018. The research was part of CAGE – Centre for Arctic Gas Hydrate, Environment and Climate funded by the Norwegian research council (grant 223259). CAGE and UiT provided full technical support in acquiring most of the data used in this thesis. Additionally, unique ...